Pragmatic, double-blind, randomised trial evaluating the impact of red blood cell donor sex on recipient mortality in an academic hospital population: the innovative Trial Assessing Donor Sex (iTADS) protocol. Issue 2 (23rd February 2021) - Fergusson, Dean A; Chassé, Michael; Tinmouth, Alan; Acker, Jason P; English, Shane; Forster, Alan J; Hawken, Steven; Shehata, Nadine; Thavorn, Kednapa; Wilson, Kumanan; Tuttle, Angie; Perelman, Iris; et al.
Abstract : Introduction: With over 1 million units of blood transfused each year in Canada, their use has a significant clinical and economic impact on our health system. Adequate screening of blood donors is important to ensure the safety and clinical benefit of blood products. Some adverse transfusion reactions have been shown to be related to donor factors (eg, lung injury), whereas other adverse outcomes have been theoretically related to donor factors (mortality and infection). Our clinical trial will test whether male donor blood leads to a greater benefit for transfusion recipients compared with female donor blood. Methods and analysis: We have designed a pragmatic, double-blind, randomised trial that will allocate transfusion recipients to receive either male-only or female-only donor transfusions. We will enrol 8850 adult patients requiring at least one transfusion at four sites over an approximate 2-year period. Randomisation and allocation will occur in the blood bank prior to release of the units of blood for transfusion. Our primary outcome is mortality. An intent-to-treat analysis will be applied using all randomised and transfused patients. The principal analysis will be a survival analysis comparing the time from randomisation to death between patients allocated to male donor red blood cells (RBCs) and female donor RBCs. Ethics and dissemination: Approval has been obtained from research ethics boards of all involved institutions, as well as from privacy offices of Canadian Blood Services, Institute for Clinical Evaluative Science and The Ottawa Hospital Data Warehouse. Our findings will be published in peer-reviewed journals and presented at relevant stakeholder conferences and meetings. Trial registration number: NCT03344887; Pre-results .